Ease and Level of use of Smartphone for Learning Amongst Pre-Service Teachers Colleges of Education in North-West, Nigeria - Abubakar Ismaila, Abdullahi; Kadage Tukur, abdullahi; Amoson Gambari, Isiaka (Universitas Terbuka, 2019)
This study Ã¢â‚¬Å“ease and level of use of smartphone for learning amongst pre-service teachers colleges of education in North-West, NigeriaÃ¢â‚¬Â was guided by two objectives, two research questions. The researchers used descriptive survey research design in the study. The researchers used mixed method (quantitative and qualitative) for data collection.Ã‚Â The population of the study was 113,030. Random sampling technique was employed to select the sample. The total population of the sample is 32,300. The entire sample that was chosen is 371 for quantitative which is in line with Raosoft sample size and 6 for qualitative. The instruments used for data collection were adopted questionnaire prediction of user acceptance and adoption of smartphone for learning with technology acceptance model questionnaire (PUAASLTAMQ) by Sek, et al, (2010) and data-blank. The frequency and percentage were employed to analyze the respondentsÃ¢â‚¬â„¢ demographic information. To answer research question one (1), descriptive statistics (frequencies and percentages) were used. To answer research question two t-test was used. The summary of the major findings indicated that smartphone is very easy to use for learning by the pre-service teachers in Colleges of Education in North-West, Nigeria and male pre-service teachers in Colleges of Education in North-West, Nigeria use smartphone for learning more than their female counterpart. The research shows that smartphone may be accepted as instructional tool in future, because the mode of smartphone operation is not difficult.Ã‚Â